THE RELATIONSHIP BETWEEN NUTRITIONAL STATUS AND PREGNANCY EXERCISE WITH HEMOGLOBIN LEVELS IN TRIMESTER III PREGNANT WOMEN - Arista, Devi (STIKES Syedza Saintika Padang, 2023)
WHO states that the prevalence of anemia in pregnant women in the world is 41.5% and 48.2% occurs in Asia, and 4% of maternal deaths in the world are due to anemia. This study aims to determine the relationship between nutritional status and pregnancy exercise on hemoglobin levels in third trimester pregnant women at Bayung Lencir Hospital, Musi Banyuasin Regency, South Sumatra Province in 2023. This research is an analytical research with a cross sectional approach. This research was conducted at Bayung Lencir Hospital, Musi Banyuasin Regency, South Sumatra Province and was carried out in January 2023. The population of this study were all pregnant women who visited Bayung Lencir Hospital from January to November 2022 with a total of 412 people and a total sample of 39 person. Samples were taken using purposive sampling technique. Data processing was carried out by univariate and bivariate analysis. The results showed that there was a relationship between nutritional status and hemoglobin levels in third trimester pregnant women p-value of 0.025, and there was a relationship between pregnancy exercise and hemoglobin levels in third trimester pregnant women p-value of 0.024. It is hoped that health workers can provide education or special health education to pregnant women regarding hemoglobin levels in pregnant women and invite pregnant women to routinely carry out pregnancy checks Keywords : Nutritional Status, Pregnancy Exercise, Hemoglobin Level